Deglobalization and Its Impact on Thai SMEs: Challenges, Opportunities, and Adaptation Strategies - Kamkankaew, Pongsiri; Thanitbenjasith, Phithagorn; Phattarowas, Vachiraporn; Khumwongpin, Surakit; Sribenjachot, Suteera (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Deglobalization, characterized by a retreat from global trade and increasing protectionism, has significantly reshaped international commerce, posing substantial challenges for Thai small and medium-sized enterprises (SMEs). These enterprises, which constitute over 99% of all businesses in Thailand and employ more than 80% of the workforce, are particularly vulnerable to these shifts in global trade dynamics. This study and aims to explore the specific impacts of deglobalization on Thai SMEs, focusing on the challenges they face, including reduced market access, supply chain disruptions, and increased costs, as well as the strategies they adopt to navigate these challenges and sustain growth. Materials and Methods: Using a document survey method, this study synthesizes existing literature and empirical evidence to provide a comprehensive understanding of how deglobalization reshapes the business environment for Thai SMEs. Results: The findings reveal that deglobalization has led to significant challenges for Thai SMEs, including increased tariffs and non-tariff barriers, geopolitical tensions affecting logistics and supply chains, and financial constraints such as reduced access to trade finance and exchange rate volatility. Despite these challenges, some SMEs have successfully adapted by exploring new export markets, diversifying their product portfolios, investing in research and development, adopting advanced technologies, and forming strategic alliances. The results highlight the critical role of innovation, market diversification, and government support in enhancing the resilience of Thai SMEs in a deglobalized world. Conclusion: Deglobalization presents both challenges and opportunities for Thai SMEs. While the increased protectionism and market fragmentation have disrupted traditional business operations, proactive adaptation strategies have enabled some SMEs to sustain growth and remain competitive. Government policies that provide financial assistance, improve infrastructure, and streamline export regulations are crucial in supporting these enterprises. Collaboration with research institutions and universities can further enhance their capacity for innovation. Future research should focus on sector-specific impacts, effective adaptation strategies, and the role of government policies in supporting SMEs in a deglobalizing global economy.